Hydraulic design of Aliabon irrigation system - Sy, Joseph T. (Animo Repository, 1993)
Executive Summary I. The Project The Hydraulic Design of Aliabon Irrigation System is a small scale water project designed to provide double-cropping of rice/diversified crops during wet and dry season. The project will provide an irrigation canal to supply water in three service areas of 450 ha. The water source will come from the Aliabon river located at Dinalupihan, Bataan.II. Irrigation Canal and Structures The main canal will have a length of 1.20 km which will branch out into right/left bank canal with a total length of 0.92 km and 7.16 km, respectively. There are five laterals with a total length of 2.05 km connected at the left bank canal. For the right bank canal, it will have eight laterals with a total length of 3.50 km. For the whole irrigation system, there are 21 shutters, 3 flow measurement structures, 4 R.C. Pipes for road crossing purposes, 1 inverted siphon to facilitate river crossing, and 2 tail escapes. III. Project cost The total project cost based on March 1993 price level is estimated at 13,439,361 Pesos. This include a contingency allowance of 10 percent and 15 percent for engineering and administration fees.